2001
DOI: 10.1521/aeap.13.1.91.18921
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Cognitive-Behavioral HIV Prevention Intervention Among HIV Negative Male Substance Abusers in VA Residential Treatment

Abstract: This investigation compared the effectiveness of a cognitive-behavioral HIV risk reduction intervention with a standard care (SC) comparison condition in modifying HIV risk related knowledge, beliefs, attitudes, and behavior at 6-month and 12-month follow-ups among 149 HIV seronegative males. The two intervention conditions were administered while participants were in inpatient alcohol and other drug abuse treatment. Global drug abuse severity, as well as injection drug abuse, decreased significantly from prei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 16 publications
0
23
0
1
Order By: Relevance
“…Examples of this work are Sorensen et al [140] and MacMahon et al [141] both of whom conclude that the brief intervention showed little additional effect on risk behaviour (see also [142]). …”
Section: Brief Interventionsmentioning
confidence: 93%
“…Examples of this work are Sorensen et al [140] and MacMahon et al [141] both of whom conclude that the brief intervention showed little additional effect on risk behaviour (see also [142]). …”
Section: Brief Interventionsmentioning
confidence: 93%
“…Em geral, as inter venções mais relatadas como eficientes foram cognitivo-comportamental, aconselhamento, entrevista motivacional e intervenção breve. A eficiência é vista por meio da apresentação da redução no uso de substâncias, tanto antes ou durante o ato sexual quanto em outros contextos, e do aumento de comportamento sexual seguro, quando esses dois fenô-menos estão associados (Jones et al, 2005;Naar-King et al, 2006;McMahon et al, 2001).…”
Section: Intervençãounclassified
“…Unfortunately, prevention efforts directed toward drug users' sexual risks have generally had lower effect sizes than those directed towards injection risk behaviors (McMahon et al, 2001;Warner and Leukefeld, 2001;Prendergast et al, 2001). In a recent meta-analysis, Semaan et al (2002) examined the effectiveness of 33 U.S.-based HIV intervention studies in reducing the sexual risk behaviors of drug users by reducing unprotected sex or increasing the use of male condoms.…”
Section: Hiv-seropositive Idusmentioning
confidence: 99%